Progressive Law Dialectics: Statesmen’s Role as Constitution Guardians and the Independence of Indonesia's Constitutional Court - Endriyani Lestari; Fitria Damayanti; Uche Nnawulezi (Universitas Negeri Semarang, 2024)
This study examines the filling of public offices with special criteria, as outlined in the constitution, which applies specifically to Constitutional Court judges. However, the term